1975
DOI: 10.1111/j.1467-8624.1975.tb03366.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Processing and Cognitive Styles in Learning-disabled and Normal Children

Abstract: A paradigm of specialized brain hemisphere processing abilities was used to test cognitive skills and cognitive style in "learning-disabled" (LD) and "normal" children. Results indicate that (1) verbal ability is not a unitary factor, and LD children are deficient in only some aspects of verbal ability; (2) the LD group perform as well as the control group on right-hemisphere tests; (3) LD boys are more field sensitive (field dependent) than the control boys; (4) LD children may be attempting to use a nonverba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Overall, the fact that the majority of studies failed to observe significant differences and that the few studies with significant findings yielded inconsistent results suggests that the significant effects obtained in children with crossed laterality are likely to be unreliable. This conclusion is consistent with the results of similar studies that were excluded from this review because they failed to provide an operative definition of crossed laterality or because they treated crossed and mixed laterality indistinctly (e.g., [ 16 , 56 , 57 , 59 , 60 , 85 ], but see [ 13 ]). Similarly, these results are also consistent with previous non-systematic reviews done in the field of laterality [ 86 , 87 ].…”
Section: Discussionsupporting
confidence: 84%
“…Overall, the fact that the majority of studies failed to observe significant differences and that the few studies with significant findings yielded inconsistent results suggests that the significant effects obtained in children with crossed laterality are likely to be unreliable. This conclusion is consistent with the results of similar studies that were excluded from this review because they failed to provide an operative definition of crossed laterality or because they treated crossed and mixed laterality indistinctly (e.g., [ 16 , 56 , 57 , 59 , 60 , 85 ], but see [ 13 ]). Similarly, these results are also consistent with previous non-systematic reviews done in the field of laterality [ 86 , 87 ].…”
Section: Discussionsupporting
confidence: 84%
“…The typical paradigm has been to dichotomize subjects on the basis of a general standardized reading comprehension test and compare groups on a traditional test of short-term memory such as digit span or word span. The research has at best found very weak relationships between span and reading comprehension (Farnham-Diggory & Gregg, 1975;Guyer & Friedman, 1975;Hunt, Frost, & Lunneborg, 1973;Perfetti & Goldman, 1976;Rizzo, 1939). Studies that have compared scanning rates in short-term memory using the S. Sternberg (1969) memory-scanning task have also found no relationship between speed of scanning and reading Comprehension (Chiang & Atkinson, 1976).…”
Section: Integration Processes and Their Time Coursementioning
confidence: 99%
“…A more accurate conceptualization of modality might be based upon the notion of attribute processing capability. Thus, the two groups of learning disabled children in this study might have differed in their ability to deal with "temporal" as opposed to "spatial" attributes (Guyer & Friedman, 1975). A careful examination of the ITPA subtests used here suggests this might be a reasonable possibility.…”
Section: Discussionmentioning
confidence: 92%